2004
DOI: 10.1002/art.20545
|View full text |Cite
|
Sign up to set email alerts
|

Aberrations in the control of quadriceps muscle force in patients with knee osteoarthritis

Abstract: Objective. To characterize the distribution of error in knee joint proprioception, quadriceps force accuracy and steadiness, and muscle strength in patients with knee osteoarthritis (OA). Special attention was paid to eccentric strength. Methods. We compared knee OA patients (n ‫؍‬ 20: 15 women, 5 men) with age-and sex-matched, symptom-free adults. Knee pain and mobility were assessed with standard tests. Knee joint proprioception was measured with a repositioning test. Quadriceps force accuracy and steadiness… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
208
7
13

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 209 publications
(240 citation statements)
references
References 48 publications
(98 reference statements)
12
208
7
13
Order By: Relevance
“…Therefore, the strength deficits in this muscle can compromise its role in absorbing loads 1,12 . Considering that individuals with knee OA usually present weakness of the quadriceps muscle, we suggest that these patients experience increased joint loading, which could contribute to increased pain.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, the strength deficits in this muscle can compromise its role in absorbing loads 1,12 . Considering that individuals with knee OA usually present weakness of the quadriceps muscle, we suggest that these patients experience increased joint loading, which could contribute to increased pain.…”
Section: Discussionmentioning
confidence: 99%
“…After receiving the test instructions, the subjects performed five maximal concentric and eccentric isokinetic contractions with a range of motion from 20° to 90° (being 0 degrees meaning full knee extension). The rest between each type of contraction was of 5 minutes duration 12 . Prior to each assessment, the subjects performed three submaximal contractions to familiarize themselves with the procedure.…”
Section: Isokinetic Evaluationmentioning
confidence: 99%
See 1 more Smart Citation
“…Increased variability of force and movement have been associated with the development of musculoskeletal disorders and pain (Madeleine 2010), such as knee osteoarthritis and subacromial impingement syndrome (Hortobágyi et al 2004;Bandholm et al 2006). Multiple neuromuscular mechanisms could be responsible for the pain-induced increase in force fluctuations.…”
Section: Multidirectional Force Fluctuations and Painmentioning
confidence: 99%
“…Increased force variability has been associated with muscle fatigue (Missenard et al 2009), ageing (Tracy 2007), increased risk of falls (Carville et al 2007), and in particular, higher force fluctuations were observed in patients with chronic musculoskeletal pain disorders such as knee osteoarthritis and subacromial impingement syndrome compared with healthy controls (Hortobágyi et al 2004;Bandholm et al 2006). Although it has been shown that pain may cause changes in muscle coordination (Graven-Nielsen et al 1997), it is still unclear how these changes affect the three-directional distribution of force variability.…”
Section: Introductionmentioning
confidence: 99%